Penentuan Kadar Natrium (Na) dan Kalium (K) dalam Buah Pisang Kepok (Musa paradisiaca L.) Berdasarkan Tingkat Kematangannya - Nurmin, Nurmin; Sabang, Sri Mulyani; Said, Irwan (Universitas Tadulako, 2018)
This study aimed to determine sodium (Na) and potassium (K) levels in the fruit of banana kepok (Musa paradisiaca L.). The method used in this study was a laboratory experiment using atomic absorption spectroscopy (AAS) instrument. The result showed that the sodium (Na) levels in unripe, ripe, and overripe bananas were 129.83 mg/kg, 125.15 mg/kg, and 122.65 mg/kg, respectively. While the potassium (K) level obtained from unripe, ripe, and overripe bananas was 266.76 mg/kg, 258.61 mg/kg, and 255.22 mg/kg, respectively. Based on these results, it can be concluded that sodium and potassium levels in unripe bananas kepok fruit were higher than in ripe and overripe bananas, moreover, the potassium levels were higher than the sodium levels.